# ################################################################### # Chapter 6, Exercise 7, page 274, GCL. # # CORRECTION: The sign in front of the term x*y^2*z should be minus (-) # rather than plus (+) as printed in the textbook. Also, a(x) is actually # a(x,y,z). # # # This is a hint for students -- not a complete solution here. ################################################################### # `mod` := mods; p := 3; # #================================================= # We want to solve F(a) = a^2 - a - r = 0 where #================================================= # r := x^6 + x^4*y^2 + x^3*z + x^2*y^4 - x*y^2*z + z^2 - 1; # #================================================= # Reduce mod I. #================================================= # Id := [y=1,z=0]; # This is our representation of the ideal I = . rmodI := eval(r, Id) mod p; # #========================================================================= # How to determine a solution in Z_3[x,y,z] / I == Z_3[x] ? #========================================================================= # # Well, note that over Z_3, (a+1)^2 = a^2 - a + 1. # # Therefore since F (mod I) takes the form # FmodI := a^2 - a - rmodI; # # we can restate the problem FmodI = 0 in the form # # (a+1)^2 = x^6 + x^4 + x^2 # = x^2 * (x^4 + x^2 + 1) # = x^2 * (x^2 - 1)^2 in Z_3[x] . # # I.e. a+1 = x * (x^2 - 1) = x^3 - x . # # Hence the desired solution a (mod I) is: # amodI := x^3 - x - 1; # #================================================= # Check this claimed solution. #================================================= # eval(FmodI, a=amodI); Expand(%) mod p; # #========================================================================= # Lifting step -- Newton's iteration: anew = a - F(a)/F'(a) . #========================================================================= # # ... try it "by hand" # ... use (6.34)-(6.35) #